DNA isolation from achieved formalin-fixed paraffin-embedded tissues in a series of 212 thyroid carcinoma cases: the influence of preanalytical factors on DNA quantity and purity. (3rd December 2019) - Nechifor-Boilă, Adela; Banescu, Claudia; Zahan, Ancuta Elena; Moldovan, Valeriu; Szasz, Emoke; Borda, Angela
Abstract : Objective: The present study aimed to investigate the influence of several important preanalytical factors (storage period of the tumor block, maximal diameter of the tumor circled area, tumor volume and tumor fraction) on the isolated DNA from formalin-fixed paraffin-embedded (FFPE) tissues in a series of thyroid carcinomas. Design: Our study included 212 FFPE blocks, archived in the Department of Pathology, Târgu-Mureș Emergency County Hospital for up to 10 years. DNA isolation was performed using a commercially available kit (MasterPure DNA purification kit, Epicentre). The DNA parameters (concentration and purity) were determined using a spectrophotometer and the Qubit 2.0 Fluorometer (Thermo Fisher Scientific) for an accurate and sensitive DNA quantification. Results: The mean DNA concentration and purity for the study cases were 489.3±372.6 ng/µl and 1.667±0.1912, respectively. The DNA concentration was correlated with the maximal diameter of the tumor circled area (p<0.0001), the tumor volume (p<0.0001) and tumor fraction (p=0.0462). No statistically significant differences both in terms of DNA concentration (p=0.374) and purity (p=0.125) in relation with the storage period of the tumor blocks were observed. When using a fluorometric quantification method, the DNA concentration was lower (mean DNA concentration: 47.15±32.85 ng/µl), but similar correlations with the morphological factors were observed. Apart for three cases, the real-time PCR amplification of the BRAF gene was successfully assessed in all cases. Conclusion: The maximal diameter of the tumor circled area, tumor volume and tumor fraction are important morphological factors that correlate with the DNA concentration and should be carefully assessed in routine practice prior to performing DNA isolation from FFPE tissues.